Profil Perbedaan Karakteristik Demografi Subjective Well-being Siswa SMK Provita Bandung - Humairah Azzahrah; Syamsu Yusuf; Ipah Saripah; M. Fiqri Syahril; Nor Zaiham Midawati Abdullah (State Islamic University (UIN) Salatiga, 2024)
The phenomenon of subjective well-being among vocational high school students has garnered considerable attention, particularly in light of the high levels of anxiety many students face due to academic and social pressures. This study aims to delineate the profile of subjective well-being among students at SMK Provita Bandung and to identify differences in subjective well-being based on demographic characteristics. Employing a comparative study method, the research involved a sample of 157 students selected through stratified random sampling. Data on subjective well-being were collected using an inventory developed by the researcher, grounded in Ed Diener's theory, and analyzed using descriptive and inferential statistical techniques (ANOVA). The findings reveal that students' subjective well-being levels are categorized as moderate across the dimensions of pleasant experiences, unpleasant experiences, and life satisfaction. No significant differences were observed in subjective well-being concerning grade level, gender, age, or ethnicity. However, noteworthy differences were found based on characteristics of social contact. These results underscore the necessity for programs to enhance students' social interactions and cultivate an environment conducive to fostering connections, ultimately improving their subjective well-being.